Penyuluhan tentang SADANIS pada Wanita Usia Subur di PMB Rama Agustina - Rama Agustina (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Breast cancer is one of the leading causes of death among women, largely due to delayed diagnosis. Early detection through Clinical Breast Examination (CBE/SADANIS) is an important strategy to identify breast cancer at an early stage. However, the level of knowledge and awareness of Women of Reproductive Age regarding SADANIS remains low. This Community Service activity aimed to improve knowledge and awareness of SADANIS among Women of Reproductive Age through health education at PMB Rama Agustina. The activity was conducted through preparation, implementation, and evaluation stages. Health education was delivered using interactive lectures and discussions, supported by educational media such as leaflets and posters. Evaluation was carried out using pre-test and post-test questionnaires to assess changes in participants’ knowledge. The results showed an improvement in participants’ knowledge and a positive change in attitudes toward the importance of early breast cancer detection. In addition, participants demonstrated increased interest and willingness to undergo SADANIS examinations, either at the midwifery practice or at nearby primary healthcare centers. In conclusion, this activity was effective as a promotive and preventive effort to support early detection of breast cancer among women of reproductive age.